Counseling Analysis of Criminal Actions on the Judge's Decision Number 55 / PID.B/2015/PN-BNA AND 79/PID.B/2013/PN.SKA. - Rini Mihartika; Rizanizarli Rizanizarli; Suhaimi Suhaimi (Budapest International Research and Critics University, 2021)
In light of the arrangements of Article 143 section (2) letter B of the Criminal System Code that the material necessities of the public prosecution should portray cautiously, obviously, and the criminal demonstration that is being accused of referencing the overall setting of the wrongdoing being perpetrated. Notwithstanding, in the choice No.55/PID.B/2015/PN-BNA and the Surakarta Locale Court Choice Number 79/PID.B/2013/PN.SKA the unmistakable components alluded to in the article have not been satisfied just as in the legitimate contemplations of the adjudicator's choice. , which doesn't plainly hold back the juridical realities uncovered at the preliminary. Since the appointed authority can't choose a case outside of the public investigator's prosecution. This composing plans to see and discover how the appointed authorities' contemplations in these 2 cases made the adjudicators just interested in 1 criminal demonstration and how the adjudicator settled on concursus. To accomplish this objective, the scientist utilizes a regulating legitimate exploration technique that leaves from lawful issues with a similar strategy. This review utilizes optional information sources comprising of essential lawful materials, auxiliary lawful materials that incorporate authority archives, books, and examination brings about the type of reports. The information was examined by subjective strategies. The outcomes showed that the appointed authority was considered unseemly in considering his choice where the sentence got by the litigant was not equivalent with what activities the respondent had submitted against the choice No.55/PID.B/2015/PN-BNA and the Surakarta Locale Court Choice Number 79/PID .B/2013/PN.SKA. It is suggested that the Public Examiner (Prosecutor) should be more cautious in setting up his arraignment as per Article 143 section (2) of the Criminal Technique Code. Similarly, the appointed authority in giving his choice. It is trusted that the appointed authority in giving the choice should contain juridical realities by considering the realities uncovered at the preliminary, so the choice given by the adjudicator doesn't contain blunders in settling on the choice, so nobody is hurt and upsets the general population by the appointed authority's choice.